VD_FINDINFO HC / 2015 / 893 vom 26. August 2015 - VD Tribunal cantonal (2015)
EXPERT, EXPERTISE, RÉCUSATION, DOMMAGE IRRÉPARABLE, DÉCISION D'IRRECEVABILITÉ | 158 al. 1 CPC (CH), 183 al. 2 CPC (CH), 321 al. 2 CPC (CH), 47 al. 1 let. f CPC (CH), 50 al. 2 CPC (CH)